O efeito do potássio (K) na formação de CH4 na reação de reforma a vapor e sua relação com a estrutura da molécula reformada - Taschin, Alan Rober (Universidade Federal de São Carlos, 2021)
Nickel (Ni) catalysts were applied in the steam reforming reaction of organic compounds. Ni is highly active for breaking C-C bonds, a route in steam reforming reactions to generate hydrogen (and CO), however it is also active for hydrogenating carbonaceous species (C, CHX and CO) to generate CH4 as a final product at low temperatures, and then the H2 yield decreases. The consequence of this unwanted reaction is related to the activation of CH4 and its conversion, which requires high temperatures, and reflects an increase in the process cost. The addition of potassium (K) to nickel catalysts suppresses the hydrogenation activity of CO to CH4. In this work, Ni/MgAl2O4 catalysts were promoted with KNO3 to reach different potassium loads and were applied in the steam reforming reaction of ethanol (SRE), butanol (SRB) and phenol (SRPh). The catalysts were characterized by nitrogen adsorption, in situ X-ray diffraction (XRD), temperature programmed reduction (TPR-H2), transmission electronic microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XANES). The catalytic evaluation was carried out in the range of 250°C - 650°C with a vapor/carbon molar ratio equal to 13. The addition of K to the catalysts weakens the Ni-O interaction, which causes agglomeration and increases the Ni nano particles size. The effect of potassium on methane formation is directly related to the structure of the reformed molecule, which determines the type of CHX species formed in the decomposition of reagents. During this step, it is expected to form CH in phenol, CH3 and CH2 in butanol and CH3 in ethanol. In K presence, methane is suppressed in CH hydrogenation, it is less expressive in CH2 species and absent in CH3 species. DFT calculations on the interaction of these absorbed CHX species in the Ni4 cluster (CHX-Ni4) with K, especially in KOH, indicates that species such as HOKHxCNi4 are stable with energy decay at -296.1, -242.4 and -27.7 kJ.mol-1 for CH, CH2 and CH3 species, respectively. The increase in adsorption heat for CH and CH2 species decreases the hydrogenation activity for methane formation.
The effect of potassium (K) on CH4 formation in the steam reforming reaction and its relationship with the structure of the reformed molecule
Keywords: Reforma a vapor; Fenol; Etanol; Potássio; Níquel; Formação de metano; Steam reforming; Phenol; Ethanol; Potassium; Nickel; Methane formation; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA